Performance analysis of linear and non-linear diversity combining techniques of FFH/BFSK communication systems - Tan, Nyit San. (2008)
The closed-form bit-error rate (BER) expressions for a uncoded fast frequency-hopped binary frequency-shift keying (FFH/BFSK) system using various diversity combining techniques in the presence of multi-tone jamming (MTJ) and additive white Gaussian noise (AWGN) conditions over a non-fading channel are obtained.